Pengaruh Tingkat Pengungkapan Corporate Social Responsibility terhadap Information Asymmetry dengan Variabel Kontrol Leverage dan Negative Earnings - Kathrin Angelin Hardy; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
There were only few studies about the affect of corporate social responsibility (CSR) on information asymmetry. The majority of research topics preveously was about the affect of CSR on financial performance. This study aimed to identify and to prove the affect of level of CSR disclosure on information asymmetry. The level of CSR disclosure was measured by using the criteria of the Global Reporting Initiative (GRI). Information asymmetry was measured by using bid-ask spread. There were two control variables used: leverage and negative earnings. This research was carried on a public companies in Indonesia which published sustainability report and listed in GRI’s database in 2008 – 2014 with a sample of 131 observations. The results showed a significant positive correlation between the level of CSR disclosure with bid-ask spread. The results also showed that leverage had significant positive affect on the bid-ask spread, while negative earnings did have affect on bid-ask spread.